Improving social protection for migrants, refugees and asylum seekers in Egypt: An overview of international practices - Marina Andrade; Lucas Sato; Maya Hammad (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Migration has been a central issue throughout Egypt's history. In addition to being a traditional country of origin and transit, its importance as a destination has been growing over the last two decades. Social protection is not always guaranteed for international migrants. UNICEF Egypt and the IPC-IG have gathered evidence of experiences that can provide insights for a new migration governance framework, a more inclusive social protection system and sustainable socioeconomic development in Egypt.
Keywords: 330; social protection; migration; governance; Egypt